Screening for physical inactivity among adults: the value of distance walked in the six-minute walk test. A cross-sectional diagnostic study - Sperandio, Evandro Fornias; Arantes, Rodolfo Leite; Silva, Rodrigo Pereira da; Matheus, Agatha Caveda; Lauria, Vinícius Tonon; Bianchim, Mayara Silveira; Romiti, Marcello; Gagliardi, Antônio Ricardo de Toledo; Dourado, Victor Zuniga (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVES: Accelerometry provides objective measurement of physical activity levels, but is unfeasible in clinical practice. Thus, we aimed to identify physical fitness tests capable of predicting physical inactivity among adults. DESIGN AND SETTING: Diagnostic test study developed at a university laboratory and a diagnostic clinic. METHODS: 188 asymptomatic subjects underwent assessment of physical activity levels through acceler- ometry, ergospirometry on treadmill, body composition from bioelectrical impedance, isokinetic muscle function, postural balance on a force platform and six-minute walk test. We conducted descriptive analysis and multiple logistic regression including age, sex, oxygen uptake, body fat, center of pressure, quadriceps peak torque, distance covered in six-minute walk test and steps/day in the model, as predictors of physical inactivity. We also determined sensitivity (S), specificity (Sp) and area under the curve of the main predic- tors by means of receiver operating characteristic curves. RESULTS: The prevalence of physical inactivity was 14%. The mean number of steps/day (≤ 5357) was the best predictor of physical inactivity (S = 99%; Sp = 82%). The best physical fitness test was a distance in the six-minute walk test and ≤ 96% of predicted values (S = 70%; Sp = 80%). Body fat > 25% was also significant (S = 83%; Sp = 51%). After logistic regression, steps/day and distance in the six-minute walk test remained predictors of physical inactivity. CONCLUSION: The six-minute walk test should be included in epidemiological studies as a simple and cheap tool for screening for physical inactivity.